Advances in accounting behavioral research. Vol. 11 - Arnold, Vicky (Advances in accounting behavioral research, 2008)
Advances in Accounting Behavioral Research publishes high quality articles encompassing all areas of accounting that incorporate theory from and contribute knowledge and understanding to the fields of applied psychology, sociology, management science, and economics. The series promotes research that investigates behavioral accounting issues. Volume 11 begins with a review article that compares the strengths and weaknesses of using a single type of research method (archival, behavioral, and qualitative) to investigate accounting phenomenon and explains why using multiple methods provides a richer understanding of particular issues. This article should provide beneficial to a wide range of researchers, not just those interested in using behavioral methodologies. The remaining articles are empirical in nature in and examine a variety of current issues. One article examines whether sophisticated financial statement users' decisions are impacted by differential treatments of stock option compensation costs while another article provides a very interesting investigation of whether investors evaluate corporate ethical behavior as a function of their relative stock market performance. Two articles examine different aspects of auditor performance, with one contrasting the performance gains by industry specialist auditors in regulated versus unregulated industries and another contrasting the perspectives of specific auditors and their colleagues on whether they possessed the attributes of an expert.Another article examines the influence of various factors that impact public accountants' exhaustion, and the final article examines whether balance scorecard performance is differentially affected by financial and nonfinancial measures. These articles are both interesting and insightful and should prove useful in facilitating future behavioral research.